FPR2 at the crossroads of inflammation and repair in the eye - da Silva, Rafael André [UNESP]; Howell, Anna; Jones-Graham, Kendra; Parween, Shama; Girol, Ana Paula [UNESP]; Farsky, Sandra H.P.; Gil, Cristiane D. [UNESP]; Vergara, M. Natalia (Elsevier, 2025)
Formyl peptide receptors (FPRs) belong to the G protein-coupled receptor family and are involved in regulating inflammatory processes, neuronal survival, and angiogenesis. In tissues such as the retina and cornea, chronic or unresolved inflammation contributes to vision loss. We review FPR2's dual, stage-dependent roles in ocular diseases, where activation by pro-resolving agonists or inhibition by antagonists can each confer therapeutic benefits. This context-specific 'on/off' potential highlights the need for precise, stage-tailored modulation. Preclinical studies demonstrate that targeting FPR2 can improve outcomes in diabetic retinopathy, keratitis, choroidal and corneal neovascularization, and re-epithelialization. We also examine the molecular mechanisms, signaling pathways, and ligand specificity that drive these divergent effects, positioning FPR2 as a promising yet complex therapeutic target in ophthalmology.